Senosios Vilniaus universiteto observatorijos biblioteka XVIII a. - Matulaitytė, Stasė (Knygotyra, 1987)
In the first of three prospective articles on the library of the old Vilnius university observatory its stock is described on the basis of the first two inventories. Five inventories presenting a census not only of furniture, tools, pictures but books as well are known. The first inventory was made in 1773–1774 when the university was taken over by the Educational Commission. It contains 624 copies with 412 different titles. The second inventory was taken down in about 1780–1781 and signed by director Martynas Počobut’s assistant Andrius Streckis. It consists of 20 publications which enriched the library. On the basis of various sources such as “A General Catalogue of Published Books of the National Library: Authors” (Paris, 1924–) and others, some catalogues and stocks of Vilnius university many publications are indentified and rewied according to centuries and countries. The two inventories show that in 30 years of its existance the observatory library has collected quite a number of valuable publications. It had Copernic’s, Kepler’s, Clairaut’s, Cassini’s, La Caile’s, Newton’s and other wellknown scientist’s works, plenty of mathematical and astronomic tables, atlases etc. No doubt the scientist’s views and thoughts made a great influence on Vilnius astronomers, whose contacts with the famous scientists and their works stimulated the Vilnius astronomers for further inventions.